The Effectiveness of Strategy Implementation for Empowering Semanggi Batik Craftsmen in Surabaya - Hardjati, Susi; Prathama, Ananta; Wahyudi, Kalvin Edo (Nusantara Science and Technology Proceedings, 2020)
Semanggi batik is the original batik of Surabaya City which has a unique cloverleaf motif. This batik is produced by a community of housewives who are members of the Family Welfare Empowerment Organization (called PKK) in Sememi Village, Benowo District. The initial goal of semanggi batik production was to improve the family economy, and was carried out on a small scale of production. However, due to the large potential demand for semanggi batik, it is necessary to empower the semanggi batik craftsman group so that the production scale can increase. In this regard, this study aims to describe the effectiveness of the implementation of the empowerment strategy that has been carried out by the Surabaya City Government to semanggi batik craftsmen. This study uses a qualitative research approach with a descriptive type. The data collection techniques used were semi-structured interviews, observation, document collection, and focus group discussions. Furthermore, the data analysis technique uses an interactive model and the data credibility test technique uses four criteria: checking the degree of trust, transferability, dependability, and certainty. The results showed that the implementation of the empowerment strategy that has been implemented by the Surabaya City Government for semanggi batik craftsmen has been quite effective. This is evidenced by several positive activities that have been carried out, such as batik training, assistance in the management of trade and brand permits, and assistance for marketing access through product displays at exhibitions and craft centers. However, it turns out that there are several obstacles in the implementation of the empowerment strategy, namely the absence of a road map for the development of semanggi batik in the future, the number of assistant craftsmen is still insufficient, and the minimum budget for assistance so there is no capital assistance, equipment, and patent registration. These constraints need to be considered and followed up so that the effectiveness of the implementation of the strategy for empowering semanggi batik craftsmen can be further improved.